PHYSICAL PERFORMANCE, TIME-MOTION, TECHNICAL-TACTICAL ANALYSES, AND PERCEPTUAL RESPONSES IN BRAZILIAN JIU-JITSU MATCHES OF VARIED DURATION (Kinesiology, 2017)
This study aimed to analyze performance, time structure, technical actions, and perceptual responses of Brazilian jiu-jitsu athletes during matches of varied duration. For this, 10 athletes were analyzed in matches of varied duration (2-min, 5-min, 8-min and 10-min). Physical tests (reaction time, maximal isometric handgrip strength, grip strength endurance, vertical jump and sit-and-reach) and perceptive scales (exertion and recovery) were applied before and immediately after a combat. The matches were recorded for technicaltacticalanalysis and to determine their time structure. The main results showed that alterations were observed for the grip strength with kimono (p=.001), whereas a decrease was observed in the suspension time in the 8-min (p=.017) and 10-min (p=.002) combats compared to pre-match mean values. The rating of perceived exertion was influenced by time (p